Pengaruh Literasi Keuangan Syariah, Religiusitas, Inklusi Keuangan Syariah, Layanan Digital M-Banking Terhadap Keputusan Menabung Gen Z. Studi Kasus Nasabah BSI Jabodetabek - Sariah; Indra (Masyarakat Ekonomi Syariah Bogor, 2024)
Islamic finance is a financial system based on the principles of Islamic sharia, which prohibits usury (interest), speculation, and investment in businesses that are considered haram. This financial system offers various products and services, such as savings, investment and financing, which are in accordance with sharia principles. In Indonesia, sharia financial institutions have developed rapidly and have become a choice for people who want to use financial services in accordance with sharia principles. Generation Z, which is a group born between the mid-1990s to the early 2010s, is known for its high technological skills and strong sharia financial values, resulting in an understanding of sharia finance and the application of these principles in financial decision making, including Saving money is important. This study aims to identify the influence of sharia financial literacy, religiosity, sharia financial inclusion, and digital m-banking services on Generation Z's saving decisions, with a focus on Bank Syariah Indonesia (BSI) customers in the Jabodetabek area. This type of research uses a quantitative approach with a sample of 135 respondents. The data analysis used is SEM-PLS assisted by the smartPLS 3 application. The results of this research show that Sharia Financial Literacy, Sharia Financial Inclusion and Religiosity have a positive and significant influence on Gen Z's Saving Decision, while the Digital Banking Services variable has no significant influence on Saving Decisions. Gen Z. This is due to several factors, including low literacy levels and internet network problems or being far from the city center.